Honda Seiroku, « Père des parcs du Japon » - Sylvie Brosseau (Projets de Paysage)
After a childhood spent in farming and studies in agronomics, Honda Seiroku (1862-1952) improves forestry in Germany from 1890 to 1892. He is part of the enlightened elite of the Meiji period – the time when the western techniques were introduced. In 1893, he became a teacher and modernised the forestry management in Japan. In 1901, he took charge of the Hibayia Park project in Tokyo – the first public park with an archetypal value. He directs the Meiji Shrine project (1915) towards the creation of a forest at the core of the city, which is considered as a model nowadays. He is at the start of the conception of many urban parks as well as national parks (1930). Through Honda’s productions, the specificities of his own course as a forester-landscaper appear – the object of a renewed reception, today.